Homologous booster immunization with an inactivated vaccine induced robust antibody response in healthcare workers: A retrospective study - Wen, Gui-Ping; Zhu, Min; Li, Li-Rong; Li, Xiu-Juan; Ye, Hui-Ming; Zhou, Yu-Lin (Frontiers in Immunology, 2023)
Coronavirus Disease 2019 (Covid-19) severely impacted the health, society, and economy around the world. With declining protective efficacy of primary vaccination and the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants, a Covid-19 booster vaccination is being fully implemented globally. Many people received three doses of BBIBP-CorV inactivated vaccine in China and other developing countries. However, the antibody response and immune persistence of the homologous BBIBP-CorV booster vaccination is yet to be thoroughly evaluated, as previous studies focused within one month after the third dose. In this study, 97 participants were enrolled to analyze the antibody response and immune persistence within 6 months as well as the safety within 7 days after the third-dose of homologous BBIBP-CorV inactivated vaccine. The seroconversion rate for total antibody against the receptor binding domain (RBD) of the SARS-CoV-2 spike (S) protein were both 100% at month 1 and month 6 after the third dose. The IgG against the RBD of the SARS-CoV-2 S protein seroconversion rate increased from 42.27% before the third dose to 100% 1 month after the third dose and then slightly decreased to 98.97% 5 months later. Positive IgM against the RBD of the SARS-CoV-2 S protein was rare and was observed in only one participant at month 1 after the third dose. The neutralizing antibody levels at month 1 and month 6 after the third dose increased 63.32-fold and 13.16-fold compared with those before the third dose, and the positive rate for neutralizing antibody was still 100% at month 6 after the third dose. Importantly, the antibody responses induced by the vaccine and immune persistence were not affected by sex or age. No serious adverse reactions were reported. Total antibody and IgG against the RBD of the SARS-CoV-2 S protein were highly correlated with neutralizing antibody, suggesting that total antibody and IgG against the RBD of the SARS-CoV-2 S protein could be used as predictors for neutralizing antibody. In conclusion, the third dose of homologous BBIBP-CorV inactivated vaccine induced a robust antibody response and moderate immune persistence. These finding are of great significance for development future vaccination strategies.